Dopamine-Induced Changes in Serum Erythropoietin and Creatinine Clearance Reflect Risk Factors for Progression of IgA Nephropathy. Issue 6 (August 2015) - Sulikowska, Beata; Johnson, Richard J.; Wiechecka-Korenkiewicz, Joanna; Korenkiewicz, Jadwiga; Marszalek, Andrzej; Odrowaz-Sypniewska, Grazyna; Manitius, Jacek
Abstract : Introduction: The infusion of low-dose dopamine is normally associated with an increase in creatinine clearance, thereby allowing one to assess renal functional reserve. Increased renal blood flow is also associated with a reduction in erythropoietin (EPO) levels. Objectives: We evaluated the use of dopamine infusion in subjects with IgA nephropathy to determine if these functional changes correlate with risk factors for progression and compared this to the renal biopsy findings. Patients and Methods: Changes in creatinine clearance and EPO levels were determined in 46 non-nephrotic IgA patients with relative preserved renal function after the infusion of low dose dopamine. Control subjects (n = 15) were evaluated using similar protocols. Results: Subjects with IgA nephropathy could be separated into those who showed a fall in EPO levels (n = 24) and those who showed no change or a rise in EPO levels (n = 22). Subjects showing the expected fall in EPO demonstrated a higher increase in creatinine clearance, similar to that observed in control subjects. Most importantly, subjects who showed a fall in EPO had less proteinuria, less N-acetyl-β-D-glucosaminidase excretion, lower serum uric acid, blood pressure, and less features of metabolic syndrome despite similar inflammation and fibrosis on biopsy as compared to the others. Conclusions: A decrease in EPO in response to dopamine is associated with a clinical phenotype that is less likely to develop progressive renal disease. These studies suggest that a fall in EPO in response to dopamine likely reflects preserved tubulointerstitial function that cannot be assessed by renal biopsy alone.